Large deflection of composite beams in bending - Mao, Shihai (2017)
The objective of this project is to derive a mathematical model to analyze large flexural deflection of composite beams with consideration of end movement. The simple beam structure made of composite material and experience large beam deflection were studied. Previous FYP experimental results of central deflection of CFRP (AX-6200-C) composite specimens with different spans 80mm, 100mm and 120mm were used as a source of comparison and validation of the mathematical model. The mathematical modelling of large deflection of composite beam is derived by defining the material property and beam geometry, using Classical Laminate Analysis method to get Young’s Modulus, utilizing Transformed stiffness to predict bending modulus EI and deriving the formula of large central deflection of beams. Subsequently, the force to cause ply failure of different layers was calculated as boundary condition of the mathematical modelling to predict the central deflection of composite beams. The graph of load P vs centre deflection δ was plotted, and the first ply failure was also included in the response curve. Finally, the experiment results and mathematical results were compared to verify the reliability of the mathematical modelling. Future work such as mathematical modelling of different composite beams, predicting of breaking point and improvement of measure instruments were recommended for further research project.